2011
DOI: 10.1007/s10620-011-1782-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Pancreatic Mass Size and Diagnostic Yield of Endoscopic Ultrasound-Guided Fine Needle Aspiration

Abstract: The sensitivity and diagnostic accuracy of EUS-FNA for solid pancreatic lesions is strongly correlated with tumor size. Sensitivity and accuracy decrease significantly for tumors that are smaller than 1 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
74
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 27 publications
6
74
0
1
Order By: Relevance
“…The presence of biliary plastic stents has been reported to diminish the rate of EUS-FNA [30], but it did not influence our results, although biliary stents were seen in about 10% of our cases, as in the other study [30]. As already known from the cytology assessment, the diagnostic accuracy of core biopsy is not related to the mass size or the presence of necrosis inside, facts previously reported also by our group [21,[31][32][33].…”
Section: Discussionsupporting
confidence: 67%
“…The presence of biliary plastic stents has been reported to diminish the rate of EUS-FNA [30], but it did not influence our results, although biliary stents were seen in about 10% of our cases, as in the other study [30]. As already known from the cytology assessment, the diagnostic accuracy of core biopsy is not related to the mass size or the presence of necrosis inside, facts previously reported also by our group [21,[31][32][33].…”
Section: Discussionsupporting
confidence: 67%
“…However, some authors have found that the sensitivity and the diagnostic accuracy of EUS-FNA of solid pancreatic lesions decreases significantly with size B2 cm [7][8][9].…”
mentioning
confidence: 99%
“…For example, tumor size has been shown to affect the diagnostic yield. 26 Fine-needle aspiration DTA studies show wide variation in accuracy, and it is possible that population differences may account for some of this variability. The role of population differences will most likely be revealed through analysis of heterogeneity in meta-analytic studies.…”
Section: Commentmentioning
confidence: 99%